Evidence of whole-body vibration exercises on body composition changes in older individuals: a systematic review and meta-analysis - Reis-Silva, Aline; Coelho-Oliveira, Ana Carolina; Moura-Fernandes, Márcia Cristina; Bruno Bessa, Monteiro-Oliveira; Batouli-Santos, Daniel; Bernardo-Filho, Mario; de Sá Caputo, Danúbia da Cunha (Frontiers in Physiology, 2023)
24 Introduction: The aging process is associated with changes in body composition, including fat gain and skeletal muscle loss from middle age onwards. Moreover, increased risk of functional decline and the development of chronic diseases are also related to aging. Objective: This systematic review and meta-analysis aimed to evaluate the effects of whole-body vibration exercise (WBVE), as a physical exercise, on body composition in people over 60 years of age. Methods: Searches were performed on PubMed, Scopus, Web of Science, and Embase. Only randomized clinical trials evaluating the effects of WBVE on body composition in older individuals were considered. The methodological quality of the studies involved was assessed using the Physiotherapy Evidence Database (PEDro) Scale, recommendations from the Cochrane Collaboration were used to assess risk of bias, and quality of evidence was assessed using the GRADE methodology. RevMan 5.4 was used to calculate standardized mean differences and confidence intervals of 95% (CIs). Results: Eight studies were included in this review with a mean methodological quality score of 7.5, which is considered high quality on the Physiotherapy Evidence Database (PEDro) Scale. The included studies suggest that more robust research with protocols and well-designed comparison groups is required to better assess changes in the body composition of older individuals through WBVE. Quantitative results were calculated, with differences in weighted means, differences in standardized means, and 95% confidence intervals (CI). Conclusion: WBVE evaluated by the studies included in this review did not demonstrate improvements in body composition, and no significant effect of WBVE was found on fat mass with standardized differences (SD = -1.92; 95% CI: -4.81 to -0.98; p=0.19), lean mass with standardized mean differences (SMD= 0.06 CI 95% [-0.21, -0.33]; p=0.67), or skeletal muscle mass with standardized differences (SD= 0.10; CI 95% [-1.62, 1.83]; p=0.91). Therefore, to date, there is not adequate evidence to state that WBVE can benefit the body composition of men and women over 60 years of age. However, further studies are required to better understand the physiological impacts of WBVE on body composition.